Peningkatan Komitmen Penanggulangan Covid-19 Mahasiswa melalui Webinar dan Deklarasi SIAGA SAKATO - Liganda Endo Mahata; Fitrisia Amelin; Fathiyyatul Khaira; Denada Florencia Leona; Andani Eka Putra; Rizanda Machmud; Irvan Medison; Hardisman Hardisman; Yefri Zulfiqar; Fenty Anggraini; Linosefa Linosefa; Desy Nofita Sari; Rahmat Syawqi (Warta Pengabdian Andalas, 2021)
The Covid-19 virus is transmitted from human to human through close contact with infected people through their respiratory droplets. A person can also be infected by touching an object contaminated with SARS-CoV-2 and then followed by reaching the eyes, nose, or mouth. Implementing the health protocol is necessary to reduce the number of virus transmissions. In addition, to increase the community's immune against Covid-19, WHO and the government have been developing a vaccination program. However, the recommendation from the latest research stated that people still have to obey the health protocol even after being vaccinated. The purpose of this community service was to help the government to increase people's understanding of the importance of implying health protocols, even after vaccination, to suppress Covid-19 cases. The method used is by holding an online event called a Webinar. It followed by a statement with audiences to commit to implementing the health protocol led by the Rector of Andalas University, then called a SIAGA SAKATO declaration. The activity began with a pre-test questionnaire for initial information collection, followed by education about Covid-19 prevention from the experts to the 512 students. The activity ended with the final data collection using a posttest questionnaire to test the student knowledge after the education. Paired t-test analysis showed a significant increase in student commitment after attending the Webinar (P≤0.05). Based on these results, the Webinar increases students' understanding of the importance of the health protocol in reducing the Covid-19 cases.